Eurosensors 2018 2019
DOI: 10.3390/proceedings2130722
|View full text |Cite
|
Sign up to set email alerts
|

Screen-Printed Microcantilevers for Environmental Sensing

Abstract: This work investigates different geometries for fully screen-printed self-actuated selfreadout microcantilevers made using a sacrificial layer process. The microcantilevers are made of PZT sandwiched between two gold electrodes. Q-factors as high as 1300 are reported. Promising theoretical sensitivities are reported (1000 Hz/µg at 620 kHz) and applications as humidity, temperature and particles sensor are explored in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…So far, different gas sensors such as field-effect transistors (FETs) [32], optical [33], electrochemical [34], surface acoustic wave [35], cataluminescence [36], microwave-based [37], quartz crystal microbalance [3], microcantilever [38] mixed potential [39,40], photonic waveguide [41], and resistive-based [42,43] have been introduced in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…So far, different gas sensors such as field-effect transistors (FETs) [32], optical [33], electrochemical [34], surface acoustic wave [35], cataluminescence [36], microwave-based [37], quartz crystal microbalance [3], microcantilever [38] mixed potential [39,40], photonic waveguide [41], and resistive-based [42,43] have been introduced in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The large positive deviation of the DustTrak 8533 by a factor of about 1.5 is not surprising. Previous studies have found that different DustTrak models over-recorded PM values by a factor of 1.2-3 (Chung et al, 2001;Grzyb and Lenart-Boron, 2019;Heal et al, 2000;Kingham et al, 2006; 2017; McNamara et al, 2011;Wallace et al, 2011;Yanosky et al, 2002) depending on the aerosol properties. It has been suggested that the "over-estimation is a simple calibration issue in which differences between the optical properties of the manufacturer's factory calibration PM (Arizona Road Dust) and the PM under study explained the uniform relative errors recorded" (Kingham et al, 2006).…”
Section: Chemical Characterisation Of Model Aerosolsmentioning
confidence: 99%
“…This requires long and expensive testing campaigns at multiple sites during different times of the year in an attempt to include all representative meteorological conditions and the temporal and spatial variations of the ambient air composition. Portable and cost-effective PM monitors, such as the DustTrak (TSI Inc., USA) and Fidas Frog (Palas, Germany), which are mostly employed for industrial or occupational hygiene surveys (Asbach et al, 2018;Davison et al, 2019;Grzyb and Lenart-Boron, 2019), outdoor (Kingham et al, 2006;Viana et al, 2015;Wallace et al, 2011) and indoor (Chowdhury et al, 2013;Manibusan and Mainelis, 2020;Zhou et al, 2016) air quality investigations, process or emissions monitoring (Al-Attabi et al, 2017;Crilley et al, 2012;Grall et al, 2018;McNamara et al, 2011), and aerosol research studies, do not necessarily go through equivalence testing. Instead, they are often calibrated in the laboratory with simple model aerosols, e.g.…”
mentioning
confidence: 99%
“…This requires long and expensive testing campaigns at multiple sites during different times of the year in an attempt to include all representative meteorological conditions and the temporal and spatial variations of the ambient air composition. Portable and cost-effective PM monitors, such as the DustTrak (TSI Inc., USA) and Fidas Frog (Palas, Hermany), which are mostly employed for industrial/occupational hygiene surveys (Asbach et al, 2018;Davison et al, 2019;Grzyb and Lenart-Boron, 2019), outdoor (Kingham et al, 2006;Viana et al, 2015;Wallace et al, 2011) and indoor (Chowdhury et al, 2013;Manibusan and Mainelis, 2020;Zhou et al, 2016) air quality investigations, process or emissions monitoring (Al-Attabi et al, 2017;Crilley et al, 2012;Grall et al, 2018;McNamara et al, 2011) and aerosol research studies, do not necessarily go through equivalence testing. Instead, they are often calibrated in the laboratory with simple model aerosols, e.g.…”
Section: Introductionmentioning
confidence: 99%